2015
DOI: 10.5380/abclima.v17i0.42413
|View full text |Cite
|
Sign up to set email alerts
|

Índice De Aridez E Tendência a Desertificação Para Estações Meteorológicas Nos Estados Da Bahia E Pernambuco (Variation and Classifiação of Aridity and Trend Desertification for Weather Stations in State of Bahia and Pernambuco)

Abstract: As alterações climáticas no mundo estão se acentuando nos últimos anos e o Brasil já vivencia mudanças associadas ao aumento da temperatura, principalmente no Nordeste. O objetivo deste trabalho foi a verificação das variações do Índice de Aridez (IA), classificação e a tendência à desertificação ao longo de 1961 a 2014, para 6 estações da Bahia e Pernambuco. Foi realizado o cálculo do Balanço Hídrico Climatológico, o do IA, a classificação climática e a tendência à desertificação, com as séries históricas obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…By conducting studies comparing AWSs and CWSs, a larger set of climate data can be obtained (which can be grouped into a single series), as is essential for studying climate change. [24] conducted a study of a 53-year historical series of climatological elements in the states of Bahia and Pernambuco, and concluded that there is a need for studies with larger data series and their responses for data spatialisation, which can be obtained by joining historical series from the two types of weather stations. In Table 2, it is observed that the measurements of the meteorological variables RH, Rs, T and ETo obtained by the AWSs and CWSs showed a good correlation (d > 0.7), statistically determined by Willmott's agreement index, while the values of R² were higher than the average classification, with the exception of Vv for the meteorological stations of Surubim and Arcoverde, with values of 0.04 and 0.31, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…By conducting studies comparing AWSs and CWSs, a larger set of climate data can be obtained (which can be grouped into a single series), as is essential for studying climate change. [24] conducted a study of a 53-year historical series of climatological elements in the states of Bahia and Pernambuco, and concluded that there is a need for studies with larger data series and their responses for data spatialisation, which can be obtained by joining historical series from the two types of weather stations. In Table 2, it is observed that the measurements of the meteorological variables RH, Rs, T and ETo obtained by the AWSs and CWSs showed a good correlation (d > 0.7), statistically determined by Willmott's agreement index, while the values of R² were higher than the average classification, with the exception of Vv for the meteorological stations of Surubim and Arcoverde, with values of 0.04 and 0.31, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A importância em analisar a variabilidade do IA é que ele pode detectar mudanças na variabilidade climática, regiões com risco de degradação do solo e até mesmo a susceptibilidade à desertificação (LOPES, 2015;FRÉCCIA, 2020;SANTOS, 2020;SILVA et al, 2020).…”
Section: Análise Da Vulnerabilidade à Secaunclassified